PENGARUH SELF ASSESSMENT SYSTEM DAN PEMERIKSAAN PAJAK TERHADAP TAX EVASION (Studi Kasus pada Wajib Pajak Badan di Kantor Pelayanan Pajak Pratama Sumedang) - Purwanto, Purwanto; Sulaeha, Teti; Safira, Hasna (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan dan Akuntansi, 2018)
This study aims to determine the impact of self-assessment system and the tax audit to tax evasion in Tax Office Sumedang, both simultaneously and partially. The study method used is quantitative method with causal relation; independent variables are self-assessment system and tax audit; dependent cariable is tax evasion. Population of this study is 6,314 Corporate Taxpayers in Tax Office Sumedang. Technique of determining the sample used is probability sampling technique with simple random sampling method, so that 100 respondents of sample number is obtained. The results of this study indicate that self-assessment system and tax audit partially impact and significantly effect on tax evasion. Self-assessment system and tax audit simultaneously have an effect on tax evasion.Â Keywords: Self-Assessment System, Tax Audit, Tax Evasion.